Phytochemical Screening of Rhizome Extract of Curcuma longa Linn. Grown in Bangladesh through GC-MS and its Bioactivities - Ferdous, Kazi Jannatul; Afroz, Farhana; Sharmin, Suriya; Islam, Md Rakibul; Mazid, Md Abdul; Sohrab, Md Hossain (Dhaka University Journal of Pharmaceutical Sciences, 2023)
The methanolic extract of Curcuma longa L. rhizome was subjected to Gas Chromatography-Mass Spectrometric (GC-MS) analysis. The chromatographic investigation of the extract showed 27 constituents of which 19 compounds were newly found from C. longa. Here, the peaks obtained in the total ion chromatogram were compared with the National Institute of Standards and Technology (NIST) database for identification of the constituents. The most plentiful component was 9-octadecenamide (Z) (5.93%). The component present in the lowest amount was 4-hydroxy-3-methoxy benzoic acid methyl ester (0.08%). The rhizome extract of C. longa and its six fractions (F1-F6) obtained through vacuum liquid chromatography (VLC) were also investigated for antioxidant, cytotoxic and antimicrobial activities.The crude extract and its fractions (F4-F6) exhibited strong antioxidant activity having IC50 values of 19.85, 18.41, 26.72 and 16.79 μg/ml, respectively compared to the standards butylated hydroxyl anisole (IC50 = 11.42 μg/ml) and ascorbic acid (IC50 = 9.01 μg/ml). Strong cytotoxicity was found in crude extract (LC50 = 1.81 μg/ml) and fractions F4 (LC50 = 2.4 μg/ml), F5 (LC50 = 2.5 μg/ml) and F6 (LC50 = 2.3 μg/ml) when compared to the standard, tamoxifen (LC50 = 0.13 μg/ml). Fractions F1-F3 displayed mild to moderate antibacterial activity against Bacillus megaterium, Staphylococcus aureus and Pseudomonas aeruginosa in comparison with the standard, Kanamycin. The compounds obtained through GC-MS may explain the above activities. The present results showed the prospect of this medicinal plant to explore further to determine the bioactive components. Dhaka Univ. J. Pharm. Sci. 22(1): 11-20, 2023 (June)